Les sociétés de plantation dans l’économie globale des services domestiques. Le cas de l’Ile Maurice - Le Petitcorps, Colette (2021)
This article looks after the specific form of exploitation in contemporary domestic service by a focus on female labour force from the plantation societies’ working class in the global economy of domestic service. The case study of Mauritius relates to the intensification of domestic service use in the context of deindustrialization and global cities’ transnational webs. Rather than exploring domestic service work from the perspective of the social reproduction and domestic economy of the served household, I consider first domestic service as a factor of production of the economic development according to Mauritian postcolonial State’s plan. The analysis of the empirical data collected during an 8 months’ fieldwork period brings together three units of analysis: the national productive context, past and present domestic service relations according to maids and employers’ representations, and the proper maids’ household. These analytical tools give evidence of the modernity of colonial power references in the making of the neoliberal exploitation of women’s time in domestic service, and of the way by which this work has turned a major site of class conflicts. This article aims to contribute to the literature on the transnational forms of exploitation in domestic service, as to the studies on the history of class relations to which the domestic workers belong.